ANALISA TINGKAT KEPUASAN NASABAH ATAS PELAYANAN JASA KEUANGAN PERDAGANGAN BERJANGKA PT. “X FUTURES” - Marwansyah, Sofyan (Universitas Bina Sarana Informatika, 2015)
Various types of services the company provides to customers either already regulated by law and that the company incentive to provide the best services to customers to improve satisfaction. In the author's purpose to analyze the level of customer satisfaction PT. X Future of the financial services of the company to test the multiple linear regression analysis using the data in the form of questionnaires to 30 (thirty) the customer. Based on the results of the discussion conducted by meode linear regression can be obtained the first result; There is a relationship between the services provided by the company to the Customer satisfaction level of 0961, where the better the service, the higher the level of Customer satisfaction is concerned because of the relationships formed between two (2) is a strong indicator, second; There is the influence of the service provided by the company to the Customer satisfaction level of 0961, where the quality of service provided greatly affect the level of satisfaction of the Customer due to the effect of which is formed between two (2) is a strong indicator and third; that the form of relevant and significant linear equation between the level of service to the Customer satisfaction level with the line equation y = -6.188 + 1,149x Keywords: Service, Customer Satisfaction